2023
DOI: 10.3389/fnbeh.2022.1051175
|View full text |Cite
|
Sign up to set email alerts
|

Development of sex- and genotype-specific behavioral phenotypes in a Shank3 mouse model for neurodevelopmental disorders

Abstract: Individuals with a SHANK3-related neurodevelopmental disorder, also termed Phelan-McDermid syndrome or abbreviated as PMS, exhibit significant global developmental delay, language impairment, and muscular hypotonia. Also common are repetitive behaviors and altered social interactions, in line with a diagnosis of autism spectrum disorders. This study investigated the developmental aspect of autism-related behaviors and other phenotypes in a Shank3-transgenic mouse model. The animals underwent two sets of identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Intriguingly, this effect was particularly notable in male neonates (Fig. 1g), consistent with existing literature indicating a higher prevalence of ASD in males compared to females, as observed in both human patients and animal models [19][20][21] .…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Intriguingly, this effect was particularly notable in male neonates (Fig. 1g), consistent with existing literature indicating a higher prevalence of ASD in males compared to females, as observed in both human patients and animal models [19][20][21] .…”
Section: Introductionsupporting
confidence: 90%
“…We unexpectedly but constantly observed male-predominant phenotypes in eShank3-KO mice, including abnormal TJ structure, increased neonatal BBB permeability, impaired neuronal excitability, and autisticlike behaviors. Although sex differences have been reported in ASD human patients and animal models [19][20][21] , the underlying mechanisms remain undetermined. Further comprehensive studies using the BBBoriented model system could contribute to elucidating the mechanisms of why the female is more protected from the genetic risk of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have suggested this test does not determine anxiety behaviors, but rather repetitive or perseverative behaviors, 38 and some mouse models with anxiety display decreased marbles buried. 39
Figure 1 The effect of psilocybin on anxiety-related behavioral tests (A) Schematic representation of experimental design, created with BioRender.com . (B) Time spent in center of open field.
…”
Section: Resultsmentioning
confidence: 99%
“…SHANK3 deficiency is known to be associated with muscular deficits ( Zhou et al, 2019 ; Lutz et al, 2020 ; Bauer et al, 2023 ). However, the pathways by which a Shank3 deletion causes these effects and whether they result in hypotonia remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this reduction, certain SHANK3 isoforms continue to be expressed ( Lutz et al, 2020 and Lutz et al, 2022 ). Based on Bauer et al, 2023 , where heterozygous and homozygous animals have been analyzed, this current study used Shank3Δ11(−/−). Using human muscle sections has limitations due to the small sample size of three patients, per age group one biopsy per individual, and the fact that they are separate individuals with genetic differences.…”
Section: Discussionmentioning
confidence: 99%